PENGOSONGAN JABATAN WAKIL LURAH DI PROPINSI DAERAH KHUSUS IBUKOTA JAKARTA: Dilema Antara Efisiensi Birokrasi dan Layanan Publik - Rahmatullah Rahmatullah (Jurnal Ilmiah Mimbar Demokrasi, 2016)
Specificity of autonomy Jakarta as the Capital of the Republic of Indonesia that is placed on the area provincial level, so that the government area consists of 5 (five) City and 1 (one) Thousand Islands District up units at the lower level, namely District and Village is a unit of government administrative and technical services. Urban Village as a government bureaucracy that deal directly with the public is the frontline in the public service. The existence of the village chief and deputy village chief was reinforced by law No. 147 of 2009 on the Organization and Work Procedure village, which strengthened the position of deputy village chief duties and functions as an auxiliary Lurah such a heavy burden of their duties to serve citizens of the capital densely populated. The reform of the bureaucracy over the birth of Jakarta Bylaw No. 12 of 2014 concerning the regional Organization still beg the question why the position of deputy village chief who is still listed in the rules of the "vacated" in all regions of Village Capital. Occurred in the dilemma between the demands of expectations as a public service town, but on the other hand the reform of the bureaucracy is still a "maintenance of structures" without "tightening" of personnel staffing.